Highly Emissive Deep‐Red Perovskite Quantum Dots in Glass: Photoinduced Thermal Engineering and Applications. Issue 11 (12th March 2021) - Sun, Ke; Tan, Dezhi; Song, Juan; Xiang, Weidong; Xu, Beibei; Qiu, Jianrong
Abstract: All‐inorganic perovskite quantum dots (QDs) have attracted enormous attention owing to their outstanding linear and nonlinear optical properties along with various promising photonic applications. Herein, 3D direct writing of CsPbI3 QDs in glass by engineering the ultrafast laser‐induced thermal effect is reported. Erasing and re‐writing along with multilayer writing are also demonstrated. The CsPbI3 QDs exhibit efficient deep‐red photoluminescence (PL) with internal quantum efficiency of 23%. The CsPbI3 QDs show strong two‐photon excited PL and optical limiting response to ultrafast laser pulses. The two‐photon absorption (TPA) coefficient is determined to be 9.76 × 10 –11  cm W −1 . Furthermore, the technique of photoinduced thermal engineering writing shows generality to pattern CsPbBr3 and CsPbCl3 QDs in glass and is also demonstrated to achieve perovskite line structures with a width of 800 nm beyond the diffraction limit. CsPbI3 QDs in glass have excellent stability under room conditions and ultraviolet light irradiation. The present technique of photoinduced thermal engineering offers a new prospect to directly construct CsPbI3 QDs in the glass. The attractive linear and nonlinear optical response of CsPbI3 QDs implies a plethora of potential applications in high‐resolution imaging, optical storage, and optoelectronic devices. Abstract : Direct writing of perovskite quantum dots (PQDs) three‐dimensionally inside the glass is achieved by engineering the ultra‐fast laser‐induced thermal effect. Besides, erasure–rewriting and multilayer writing of PQDs can be controlled by the thermal accumulation in ultra‐laser writing. The as‐prepared CsPbI3 PQDs exhibit stable linear and nonlinear deep‐red photoluminescence with an internal quantum efficiency of 23%.